Triangle of Care Standards Incorporation and Audit Implementation to Optimise Carer Involvement and Support Services Across Psychiatric Rehabilitation and Acute Wards at Cygnet Churchill Hospital London - Angela Misra; Omer Malik; Laura Sheridan; Derek Tracy (BJPsych Open)
Aims: UK National Institute for Health and Care Excellence Guidelines recognise the importance of effective family and carer involvement in ensuring good patient care and outcomes.